Multidisciplinary engineering systems : design and optimization techniques and their application - Leondes, Cornelius T. (Control and dynamic systems, 1993)
Control and Dynamic Systems V57: Multidisciplinary Engineering Systems: Design and Optimization Techniques and Their Application.